2008
DOI: 10.1177/1078345808318217
|View full text |Cite
|
Sign up to set email alerts
|

An HIV, STD, and Hepatitis Prevention Program for Young Men Leaving Prison: Project START

Abstract: The rates of HIV, STD, and hepatitis infection are high among persons entering prisons, and many of these persons engage in high-risk behaviors after release. Therefore, innovative programs that reduce risk behaviors after release are urgently needed. Project START developed and evaluated two interventions designed for young men leaving prison. This article describes both interventions: the single-session intervention and the enhanced intervention. The single-session intervention focused on HIV/STD/hepatitis p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…This RB process used is designed to empower both the service-user (young men in prison) to take responsibility to improve their own health and agents of state (duty-bearers—nurses) to fulfill their obligations under human rights legislation to provide appropriate and accessible health and education [12]. Such an inclusive approach can reduce the young men’s risk behaviors upon release and assist with their reintegration back into the community [66]. Working within the prison environment and employing an RB approach provided an opportunity to work with a group of marginalized young men and support and advance the concept of healthy prisons [20,28,41], that is, to reinforce the idea that prison health is public health and that prisoners should benefit from rehabilitation strategies that empower them to be released back into the community in better health than they entered, for the good of themselves, their families, and communities [2,23,25,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…This RB process used is designed to empower both the service-user (young men in prison) to take responsibility to improve their own health and agents of state (duty-bearers—nurses) to fulfill their obligations under human rights legislation to provide appropriate and accessible health and education [12]. Such an inclusive approach can reduce the young men’s risk behaviors upon release and assist with their reintegration back into the community [66]. Working within the prison environment and employing an RB approach provided an opportunity to work with a group of marginalized young men and support and advance the concept of healthy prisons [20,28,41], that is, to reinforce the idea that prison health is public health and that prisoners should benefit from rehabilitation strategies that empower them to be released back into the community in better health than they entered, for the good of themselves, their families, and communities [2,23,25,26,28].…”
Section: Discussionmentioning
confidence: 99%
“…Future research should investigate the effectiveness and efficacy of different intervention styles to determine which programs would be the best fit for use in correctional facilities. Although only one study reported a cost analysis (Grinstead et al, 2008), this information would likely impact which programs have the potential for replication in other environments. While every type of intervention included had some degree of significant results for its HIV prevention interventions, more research can be done on the methods of delivery such as individual or group styles, face-to-face or telephone, peer-led, lecture or participatory classrooms, or video-based interventions.…”
Section: Discussionmentioning
confidence: 99%
“…It is common among large, grant-funded intervention studies that multiple articles are published that describe unique aspects of the overall study (i.e., studies that report the theoretical design/rationale of a study, studies that report various outcome measures, or studies that report cost/benefit analyses). To address this limitation, we attempted to find additional articles and were able to locate five that describe the intervention, rationale, or cost analysis of these studies (Fasula et al, 2013; Grinstead et al, 2008; Inciardi et al, 2007; Johnson et al, 2013; Leukefeld et al, 2009). It should be noted that, however, as with other reviews of the literature, we may have missed some studies due to our search strategy.…”
Section: Discussionmentioning
confidence: 99%
“…This article reviews the literature on promising HIV prevention programs in prison and reports on results of a survey among state prison officials of the HIV prevention policies in their state prison systems. Evidence-based HIV risk reduction programs in prisons and jails with community follow-up range from a brief DVD-based intervention (Inciardi et al, 2007) to one-on-one risk counseling (Project START; Grinstead et al, 2008; Wolitski, 2006). Other programs focus on certain subpopulations such as adolescent males leaving jail (REAL Men; Freudenberg et al, 2010) and injection drug users (Project ARRIVE; Barreras & Drucker, 2009; Wexler, Magura, Beardsley, & Josepher, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Peer-led prevention programs will be most effective if they are targeted at behaviors in the community, where most inmates with HIV are infected, rather than at behaviors in prison (Hammett, 2006). Research has shown that peer-based HIV education programs that link returning prisoners to follow-up services in the community can reduce HIV risk behavior; two such programs are Project START (Grinstead et al, 2008) and Project Bridge (Zaller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%